4CPS-005 Evaluating pharmaceutical logistics automated technologies in the hospital setting: a health technology assessment (HTA) approach. (23rd March 2022) - Foglia, E; Garagiola, E; Ferrario, L; Bellavia, D; Schettini, F; Asperti, F; Porazzi, E
Abstract : Background and importance: Automation of hospital medication management demonstrated advantages to wards manual systems, especially in error reduction, improving patient safety and ensuring drugs' traceability. Despite the existence of literature on benefits, no multidimensional evidence on automation of hospital medication management is available. Aim and objectives: The study aimed to demonstrate the value of four scenarios of automated technologies' introduction, with a comprehensive health technology assessment (HTA) approach, comparing: (1) manual dispensing, (2) presence of only centralised automated systems in the hospital pharmacy, (3) presence of only decentralised automated systems in the wards and (4) integration of scenarios 2 and 3 into a full solution, with electronic prescription. Material and methods: The HTA involved 50 healthcare professionals (pharmacists, nurses, decision-makers and other professionals) in four European countries in 2021. After a structured literature review, the nine domains of the EunetHTA Core Model were deployed using validated questionnaires (with a seven-item Likert scale). Differences among groups and scenarios were studied by ANOVA test. All analyses were conducted considering a level of significance equal to 0.05 and were performed using IBM SPSS software (Version 22.0). Results: Results from the efficacy and safety questionnaires showed that the presence of automation resulted in a decrease in dispensing errors (1.75, 1.20, 1.88, 2.19, respectively, for scenarios 1, 2, 3, 4; p value = 0.000) and consequently in adverse events (–2.13, 1.18, 1.71, 2.46, respectively, for scenarios 1, 2, 3, 4; p value = 0.000), especially if associated with electronic prescribing, confirming the literature findings. A low organisational impact of automation was registered (–0.71, 0.50, 0.49, 0.63, respectively, for scenarios 1, 2, 3, 4) due to a trade-off between technological change efforts and efficiency beneficial effects in the first year. Ethical and social dimension results demonstrated a positive impact of automation (–0.93, 0.72, 1.03, 1.23, respectively for scenarios 1, 2, 3, 4; p value = 0.000) on patients' perceived quality of life. The impact on drugs thefts and the identification of responsibility in cases of legal controversies were the most appreciated legal items. Conclusion and relevance: In a literature dominated by safety evidence on automated solutions, a complete HTA approach demonstrates its validity in communicating and demonstrating multidimensional and multidisciplinary values of hospital automated dispensing solutions. References and/or acknowledgements: Conflict of interest: No conflict of interest